Understanding the sufficiency of community based nutritional interventions: a social determinants perspective - Prakash Babu Kodali (Al Ameen Medical College, 2017)
Back ground: The relationship between socio-economic determinants and health is well known, and it is well established particularly with respect to malnutrition. Importantly, the health of those who are at the lowest strata such as those belonging to deprived social classes and women is worst hit. Considering that women face health inequities the most, the government of India launched "Rajiv Gandhi scheme for empowerment of adolescent girls" also called as "Sabala Yojana". Objectives: The current study attempted to understand the interplay of the socio-economic determinants, in a national programme context and explain how they influence the utilization of benefits of Sabala Yojana by adolescent girls. Methodology: The study utilized a Quantitative led qualitative mixed-methods approach. Structured questionnaire was used for quantitative data collection whereas In-depth Interview guides were used for qualitative data collection. Descriptive and Inferential statistics were used for quantitative data analysis, thematic analysis was adopted for qualitative data analysis. Results: Quantitative Results: Mean BMI = 16.29 (N= 219), SD = ± 2.79. Regression Analysis BMI and Caste of Individual: Constant (b0)= 14.496, (t)= 78. 270, p ≤ 0.01 (r2 = 0.580) .for OC, OBC and Other caste groups (b)= 4.275, (t) 17.299, p≤ 0.01; BMI and Income: Constant (b0)=10.162, (t) = 22.493, p ≤ 0.01 (r2 = 0.53). for income (b)= 0.01, (t) = 15.55, p ≤ 0.01. Qualitative Results: Regularity of supplies, overburdening because of multiple programmes, poverty, lack of proper storage facilities, quality of the nutritional supplements, Utilization of Supplements for Household needs and Iniquitous utilization of supplies at household level were the emergent qualitative themes. Conclusion: The results of the study show that though the nutrition supplementation programmes provide considerable inputs, the efficient utilization of benefits is influenced by several social determinants, which if unchecked makes the success of the programme non-achievable.